Integrated environmental impact assessment: a Canadian example - Kwiatkowski Roy E.; Ooi Maria (The World Health Organization, 2003)
The Canadian federal process for environmental impact assessment (EIA) integrates health, social, and environmental aspects into either a screening, comprehensive study, or a review by a public panel, depending on the expected severity of potential adverse environmental effects. In this example, a Public Review Panel considered a proposed diamond mining project in Canada's northern territories, where 50% of the population are Aboriginals. The Panel specifically instructed the project proposer to determine how to incorporate traditional knowledge into the gathering of baseline information, preparing impact prediction, and planning mitigation and monitoring. Traditional knowledge is defined as the knowledge, innovations and practices of indigenous and/or local communities developed from experience gained over the centuries and adapted to local culture and environment. The mining company was asked to consider in its EIA: health, demographics, social and cultural patterns; services and infrastructure; local, regional and territorial economy; land and resource use; employment, education and training; government; and other matters. Cooperative efforts between government, industry and the community led to a project that coordinated the concerns of all interested stakeholders and the needs of present and future generations, thereby meeting the goals of sustainable development. The mitigation measures that were implemented take into account: income and social status, social support networks, education, employment and working conditions, physical environments, personal health practices and coping skills, and health services.